Fiqh Sosial Paradigm for Understanding Universal Values of Pancasila - Tutik Nurul Janah; Siti Nur Ami'in (Santri: Journal of Pesantren and Fiqh Sosial, 2023)
This paper is the result of research on interpreting universal values ​​of Pancasila according to the paradigm of fiqh sosial. This research is a qualitative research. This research uses a descriptive method. The Fiqh Sosial paradigm refers to the thoughts of Kiai Sahal Mahfudh who believes that the purpose of human existence in this world is to get happiness in the world and heaven. This goal will be achieved if humans do not separate the implementation of the two functions. Namely the function ibadatullah and fungsi imaratul ardli. The first precept of Pancasila which contains religious values ​​is a function of ibadatullah which will always be connected with the other four precepts. The first precept of Pancasila, which is the spirit of the other precepts, also shows the compatibility of understanding that the function of ibadatullah is the basis for the important task of humans in caring for the universe (imaratul ardli). This study aims to provide insight to the public about the paradigm of social fiqh in interpreting the universal values of Pancasila.